2014
DOI: 10.23953/cloud.ijavst.189
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Avian Metapneumovirus Infection in Broiler Breeder Chicken Farms in Tamil Nadu

Abstract: Avian metapneumovirus (aMPV) is an important poultry pathogen causing an acute highly contagious upper respiratory tract infection in chickens leading to swollen head syndrome. The disease can cause significant economic losses in turkey and chicken flocks, particularly when exacerbated by secondary pathogens. The purpose of this study was to determine the prevalence of avian metapneumovirus antibodies in broiler breeder flocks in Tamil Nadu, India. Twenty numbers of broiler breeder farms located in Tirupur dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In a recent study in Ahwaz, in the south west of Iran, Mayahi and colleagues reported 55.5% aMPV seropositivity [31]. Similarly, Eswaran et al reported seroprevalence of aMPV in breeders (34%) of Tamil Nadu in India [32]. The virus has clearly circulated in the region.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study in Ahwaz, in the south west of Iran, Mayahi and colleagues reported 55.5% aMPV seropositivity [31]. Similarly, Eswaran et al reported seroprevalence of aMPV in breeders (34%) of Tamil Nadu in India [32]. The virus has clearly circulated in the region.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study in Bangladesh, Ali et al (2019) observed that 53.29% chicken harbored antibodies against aMPV and incidence was higher in broiler breeders more than 41 week of age. In India an earlier study in Tamil Nadu State (Eswaran et al, 2014) observed 34.02% antibodies in broiler breeder chicken. Our findings are also in concurrence with these findings however, the 9.88% positivity observed in our study is lower as compared to earlier studies this could be due to difference in biosecurity measures followed in the farms sampled.…”
Section: Resultsmentioning
confidence: 93%
“…The virus may also adversely affect egg production in breeder chickens and commercial layers (Cook et al, 2000, Jones et al, 1991. In India, avian metapneumovirus antibodies have been detected in broiler breeder flocks of seven States where in, 32.12-34.02% of tested birds were positive to aMPV antibodies (Eswaran et al, 2014, Surajit et al, 2018. In India data regarding aMPV status in layers is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the antibody titer, the incidence was 73.1% in chickens in Korea [38]. The rates in Bangladesh and Tamil Nadu state in India were 53.29% and 34.02%, respectively [39,40]. In Ukraine, 78% of turkeys and 100% of "Birkivska Barvysta" hens were aMPV carriers [41].…”
Section: Discussionmentioning
confidence: 99%